Product Line Engineering Comes to the Industrial Mainstream. Issue 2 (21st August 2019) - Clements, Paul C.
ABSTRACT: Product line engineering (PLE) is a systems engineering discipline to engineer a portfolio of related products in an efficient manner, taking full and ongoing advantage of the products' similarities while respecting and managing their differences. Managing a portfolio as a variable single entity, as opposed to multiple separate products, brings enormous efficiencies in production and maintenance. This paper shows that PLE has now matured into a repeatable, industrial‐strength engineering discipline. We define and explore the concepts central to modern product line engineering and illustrate how it applies in two of the most challenging systems engineering domains: aerospace and defense, and automotive.